Self‐Supported Pd Nanorod Arrays for High‐Efficient Nitrate Electroreduction to Ammonia. Issue 10 (22nd January 2023) - Guo, Heng; Li, Mengyue; Yang, Yuantao; Luo, Rui; Liu, Wei; Zhang, Fengying; Tang, Chun; Yang, Guidong; Zhou, Ying
Abstract: Electrochemical nitrate (NO3 − ) reduction to ammonia (NH3 ) offers a promising pathway to recover NO3 − pollutants from industrial wastewater that can balance the nitrogen cycle and sustainable green NH3 production. However, the efficiency of electrocatalytic NO3 − reduction to NH3 synthesis remains low for most of electrocatalysts due to complex reaction processes and severe hydrogen precipitation reaction. Herein, high performance of nitrate reduction reaction (NO3 − RR) is demonstrated on self‐supported Pd nanorod arrays in porous nickel framework foam (Pd/NF). It provides a lot of active sites for H* adsorption and NO3 − activation leading to a remarkable NH3 yield rate of 1.52 mmol cm −2 h −1 and a Faradaic efficiency of 78% at −1.4 V versus RHE. Notably, it maintains a high NH3 yield rate over 50 cycles in 25 h showing good stability. Remarkably, large‐area Pd/NF electrode (25 cm 2 ) shows a NH3 yield of 174.25 mg h −1, be promising candidate for large‐area device for industrial application. In situ FTIR spectroscopy and density functional theory calculations analysis confirm that the enrichment effect of Pd nanorods encourages the adsorption of H species for ammonia synthesis following a hydrogenation mechanism. This work brings a useful strategy for designing NO3 − RR catalysts of nanorod arrays with customizable compositions. Abstract : The self‐supported Pd nanorod arrays on the nickel foam provide high‐concentration active sites and electron transport channels for electrochemical nitrate reduction reaction (NO3 ‐ RR). The enrichment effect of Pd nanorods encourages the adsorption of H species for ammonia production following a hydrogenation mechanism. This work brings a useful strategy for controlling pollution and obtain more valuable ammonia.